Ideologi Islam dalam Kebijakan Redaksional Harian Umum Republika: Analisis Wacana Kritis tentang Pemberitaan Konflik PKB dan Film Fitna - M. Exsa Firmansyah (Jurnal Komunikasi, 2008)
This research focus on Islamic ideology in the redactional policy, that was one of the internal factor when creating a Republika news product towards PKB conflict, Ahmadiyah cult and Fitna controversy. The analysis of content at PKB’s conflict was shown Republika’s neutral display. Its neutral display was shown by the theme, the option of people who was being the source. While, at the Fairclough text analysis, Republika was shown the negative effect from that conflict which didn’t have the good effect for two sides, but could bring the negative effect for the party. For the news of Ahmadiyah, the content analysis was shown Republika’s position as one side which against Ahmadiyah with used perception that Ahmadiyah is untrue side. From the research the researcher done, there's a conclusion that islamic ideology in the Republika redactional policy, can be categorized as the form of conservative Islamic ideology.